2016
DOI: 10.4140/tcp.n.2016.161
|View full text |Cite
|
Sign up to set email alerts
|

Assessed Value of Consultant Pharmacist Services in a Home Health Care Agency

Abstract: Clinicians indicated consultant pharmacist services are beneficial and they used the consultant pharmacist primarily for pain management, drug side effects, and drug interactions, but made referrals for a wide range of reasons. This indicates that an onsite consultant pharmacist is valuable to home care providers. Further research regarding the benefit of an onsite consultant pharmacist in the home care setting is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…Our study is the first in Australia to quantify MRPs and medication treatment authorization discrepancies for at‐risk home nursing clients, and to explore the integration of a clinical pharmacist within a home nursing service . There has been no previous research into the role of pharmacists integrated within home nursing services in Australia, and only a few studies internationally, mainly in the USA and UK, within home healthcare services …”
Section: What Is New and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study is the first in Australia to quantify MRPs and medication treatment authorization discrepancies for at‐risk home nursing clients, and to explore the integration of a clinical pharmacist within a home nursing service . There has been no previous research into the role of pharmacists integrated within home nursing services in Australia, and only a few studies internationally, mainly in the USA and UK, within home healthcare services …”
Section: What Is New and Conclusionmentioning
confidence: 99%
“…integrated within home nursing services in Australia, and only a few studies internationally, mainly in the USA and UK, within home healthcare services. [32][33][34] . Findings from those studies suggested that patients who received a pharmacist review were less likely to have a hospital admission or emergency room visit and hence was likely to be cost-saving.…”
Section: What Is Ne W and Con Clus I Onmentioning
confidence: 99%
“…The only related home care-based clinical pharmacy models we identified in the published literature were services delivered within some home healthcare services in the USA 9 31–33 and a domiciliary pharmacy service provided by a community health and social care service in the UK. 34 In the USA, Redit et al described a home healthcare pharmacist role that included pharmacist home visits, medication reconciliation and medication review.…”
Section: Discussionmentioning
confidence: 99%
“…Уровень участия фармацевтических работников в про-цессе лечения пациентов различный и значи-тельно варьирует от страны и самой организа-ции. Так, например, в Washington State University реализуется совместное ведение на этапе амбу-латорной и домашней помощи, оценки боли и по-бочных эффектов, указания на необходимость посещения узкого специалиста [2]. В универси-тетах Флориды и Колорадо проводилось иссле-дование совместной работы врача и фармацевта с целью повышения эффективного контроля ар-териального давления у пациентов [3].…”
Section: фгбоу во «дальневосточный государственный медицинский универunclassified